2016
DOI: 10.1016/j.fuel.2016.06.100
|View full text |Cite
|
Sign up to set email alerts
|

The influence of asphaltene-resin molecular interactions on the colloidal stability of crude oil

Abstract: g r a p h i c a l a b s t r a c t Micellar structure of asphaltene in a dispersing medium of lighter resins, aromatics, and saturates. a b s t r a c tIn the colloidal hypothesis of vacuum residua and asphalt, micelles are assumed to have an asphaltenic core with the greatest weight and aromaticity and an outer shell composed of lighter and less aromatic molecules. The true nature of the micelles, and the asphaltenic core in particular, has always been a debatable issue among asphalt researchers. One of the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 90 publications
3
66
0
3
Order By: Relevance
“…This is in agreement with the results obtained by recent quantum mechanical calculations. 57 A shoulder occurs at about 0.9 nm for the PMF curve under vacuum, corresponding to the offset structure of the asphaltene dimer. 20 The PMF reaches a steady value in scCO 2 as the separation between them is about 0.6 nm.…”
Section: Potential Of Mean Forcementioning
confidence: 97%
“…This is in agreement with the results obtained by recent quantum mechanical calculations. 57 A shoulder occurs at about 0.9 nm for the PMF curve under vacuum, corresponding to the offset structure of the asphaltene dimer. 20 The PMF reaches a steady value in scCO 2 as the separation between them is about 0.6 nm.…”
Section: Potential Of Mean Forcementioning
confidence: 97%
“…showed that resin-asphaltene interactions are prominent only if the number of resin molecules is greater than the number of asphaltene molecules [36]. The empirical ratio Resins (wt%)−0.4×Asphaltenes (wt%) ν involves and demonstrates the above-mentioned effects of resin and asphaltene on surfactant adsorption coefficients.…”
Section: Resultsmentioning
confidence: 90%
“…In actual fact, consolidated asphaltene films around the droplets of emulsion do not coalesce after certain aging times. Obviously, adsorption kinetics and MD studies play a key role in the mechanical properties of films and an asphaltene adsorption with diffusion controlled at short times with individual molecules, transitioning possibly to a barrier-controlled regime in which larger aggregates are involved, 14 all of which helps in understanding the interfacial phenomena system assisting in the area development.…”
Section: Resultsmentioning
confidence: 99%